Manajemen Risiko Pembiayaan pada Bank Syariah 2018-2022: Literature Studies - Ahmad Agus Hidayat; Achmad Muzakki; Muhamad Ahsan; Alfa Saniyah (Universitas Wahid Hasyim Semarang, 2023)
Financing risk management in Islamic banks has been widely discussed in scientific articles, both nationally accredited and unaccredited. The purpose of this research is to see the extent of the application of financing risk management in Islamic banks in Indonesia and to find out the financing model that is most attractive to customers. In this research, the method used is through a qualitative content analysis approach. The results of this study state that the majority of financing in Islamic banks in Indonesia have implemented risk management through 4 stages, namely, risk identification, risk measurement, risk monitoring and finally risk control. While the financing contract that most customers are interested in using the murabahah contract, the main reason is because in this contract the risks faced are the least compared to other contracts, if from the bank's perspective with the amount of customer interest in the murabahah contract, of course the benefits it gets tend to be the biggest compared to other contracts. In addition, the bank also avoids the risk of accepting defaults from customers, because in murabaha customers still have an obligation to pay in a state of profit or loss.Keywords: Risk Management; Sharia Banks; Literature StudyAbstrakManajemen risiko pembiayaan pada bank syariah telah banyak dibahas diberbagai artikel ilmiah, baik yang sudah terakreditasi secara nasional ataupun belum terakreditasi. Tujuan penelitian ini untuk melihat sejauh mana penerapan manajemen risiko pembiayaan pada bank syariah di Indonesia serta mengetahui model pembiayaan yang paling diminati nasabah. Metode yang digunakan pada penelitian ini adalah konten analisis. Hasil penelitian menunjukkan bahwa mayoritas pembiayaan pada bank syariah di Indonesia telah menerapkan manajemen risiko melalui 4 tahapan yakni, identifikasi resiko, pengukuran resiko, pemantauan resiko dan pengendalian risiko. Sedangkan akad pembiayaan yang paling banyak diminati nasabah adalah akad murabahah karena pada akad tersebut risikonya paling rendah bila dibandingkan dengan akad lainnya. Jika ditinjau dari perspektif Bank, akad murabahah memberi keuntungan yang paling tinggi dibandingkan akad lainnya. Disamping itu risiko gagal bayar dari nasabah rendah, karena nasabah tetap memiliki kewajiban membayar kewajibannya dalam keadaan untung ataupun rugi.